Policy Implementation Direct Cash Assistance Program in Corona Virus Disease (COVID-19) in Tondegesan Village Kawangkoan Sub District - Fitri H Mamonto; Thelma Wawointana; Gloria Ervinsky Moningka (Universitas Muhammadiyah Gorontalo, 2021)
This research aims at how the Village Fund Direct Cash Unity program in the 2019 Corona Dessease Virus pandemic (Covid-19) In Tondegesan Village, Kawangkoan District, this research uses a qualitative approach method, and uses data techniques: observation, interviews and documentation, with data sources are : The Tondegesan Village Government and the Tondegesan Village Community, with the results of the research showing 1). The standards and targets that defined the criteria set did not qualify as BLT-DD recipients. 2) Characteristics of Implementers related to the nature and tendency of implementers in the distribution of BLT-DD to go through various stages carried out through village meetings 3) The communication between the village government and the community is due to the absence of socialization from the village government regarding the BLT-DD program. For request 1) Need to be implemented as much as possible with existing standards and the right target. 2) The village government must be more objective in determining the beneficiary families of BLT-DD according to the established criteria. 3) Communication is needed in creating a harmonious relationship.